Peningkatan Penguasaan Konsep Siswa Melalui Model TGT (Team Games Tournament) Berbantuan Media Ular Tangga - Mahfuzah Mk, Atiq Elifia; Wahyuni, Eva Ari; Yamin, Yamin; Sutarja, Maria Chandra; Hartiningsih, Try (Natural Science Education Research, 2025)
This study was conducted because of the low mastery of student concepts caused by the lack of variation in learning models and media. This study aims to determine the increase in student concept mastery after the TGT model assisted by snakes and ladders media is applied. This study is a quantitative study using One Group Pretest-Posttest Design. This study was conducted at UPTD SMP Negeri 3 Bangkalan with a sample of class VII D. The research data collection technique used a concept mastery test. The data analysis technique used was the N-Gain test. The results of the study that can be concluded are that there is an increase in student concept mastery as evidenced by the average N-Gain score of 0.47 which is categorized as moderate.